PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI ASN PADA DINAS LINGKUNGAN HIDUP KABUPATEN PONOROGO - Fahmi, M. Fitrul; Wahyudi, Amin; Suprayitno, Suprayitno (Universitas Slamet Riyadi, 2019)
The general objective of this study was to examine and analyze the influence of leadership style, and work culture on organizational commitment, with job satisfaction as an ASN mediating variable at the Department of the Environment of Ponorogo Regency. Specific objectives are to test and analyze: (1) the influence of leadership style on job satisfaction, (2) work culture on job satisfaction, (3) the influence of leadership style on organizational commitment, (4) the influence of work culture on organizational commitment, (5) the effect of job satisfaction on organizational commitment, (6) job satisfaction mediates the influence of leadership style on organizational commitment, and (7) job satisfaction mediates the influence of work culture on organizational commitment. The population in this study were all ASN Ponorogo Regency Environmental Services as many as 89 people. In this study using the census method. This research data is primary data by filling out the questionnaire by respondents. After the data has been collected, an instrument test consisting of the validity test and the reliability test with Cronbach Alpha. Then the t test, F test, R2 test, hypothesis test are performed. analysis techniques using linear regression, descriptif analysis, and path analysis.The results showed that 1) the influence of positive and significant leadership style on job satisfaction, (2) the influence of positive and significant work culture on job satisfaction, (3) the influence of positive and significant leadership style on organizational commitment, (4) the influence of positive work culture and significant on organizational commitment, (5) positive and significant effect on job satisfaction on organizational commitment, (6) job satisfaction mediates the influence of leadership style on organizational commitment, and (7) job satisfaction mediates the influence of work culture on organizational commitment.